(untitled) (Agroindustrial Science, 2019)
Fishery resource Engraulis ringens “anchovy” bioeconomy sustainability is being affected by El Niño climate event whose intensities ranges from very strong, weak and moderate along the Peruvian coast. Paita, Chimbote, Huacho, Callao, Pisco and Ilo fishing ports were hit by “El Niño” from weak to moderate intensities in the years 2002-2003, 2006; 2008-2009. This caused Chimbote to deliver a production volume of 334.320 tons which represents the biggest bioeconomy sustainability in 44% with a value of 232.770 x 106 million USD.